Stakeholder theory and internal marketing communications: a framework for analysing the influence of new media - De Bussy, Nigel; Ewing, M.; Pitt, L. (Routledge, Taylor and Francis, 2003)
Effective two-way communication is widely viewed as an essential component of successful internal marketing strategies, yet little research has so far been conducted on the relative merits of different communication media in an internal marketing context. Since the mid-1990s Internet technologies have revolutionized internal communications in many organizations. However, the impact of these new forms of electronic media on internal marketing communication remains relatively unexamined. This paper draws on stakeholder and communication theories to provide a framework for understanding the dimensions of effective internal marketing communications and presents the results of an empirical study on the relationship between these dimensions and the use of new media in the workplace.